ACUTE MACULAR NEURORETINOPATHY AFTER RANIBIZUMAB INJECTION IN A DIABETIC PATIENT. (2017) - Wheatley, H. Matthew; Sarraf, David
Abstract : Purpose: To report a case of acute macular neuroretinopathy occurring after intravitreal ranibizumab injection for diabetic macular edema. Methods: Observational clinical case report. Results: The patient received an intravitreal ranibizumab (0.3 mg) injection for diabetic macular edema. Three days later, he had a decline in vision associated with a central and paracentral scotoma. Optical coherence tomography (OCT) demonstrated bandlike hyperreflectivity of the outer nuclear and plexiform layers corresponding to the patient's scotoma, consistent with the diagnosis of acute macular neuroretinopathy. There was spontaneous resolution of the abnormalities observed in optical coherence tomography, but only partial resolution of the scotoma was observed 4 months after presentation. Conclusion: Diabetic retinopathy may be associated with acute macular neuroretinopathy. The temporal relationship between ranibizumab injection and the onset of acute macular neuroretinopathy in this case report raises the possibility of a causal relationship. Abstract : This is a case report of a patient who developed acute macular neuroretinopathy after intravitreal ranibizumab injection for diabetic macular edema. Diabetic microvasculopathy may be a risk factor for acute macular neuroretinopathy, but a causal relationship between ranibizumab injection and acute macular neuroretinopathy seems unlikely.